Dynamic characteristics after bias stress of GaN HEMTs with field plate on free‐standing GaN substrate. Issue 15 (2nd May 2021) - Ma, Qiang; Ando, Yuji; Wakejima, Akio
Abstract: This paper investigates the electron trapping behaviour after bias stress in GaN high‐electron‐mobility transistors (HEMTs) fabricated on GaN substrate. On‐resistance ( R ON ) and electron‐trap‐induced threshold voltage shift (Δ V th ) of GaN HEMTs on GaN substrate are determined by gate quiescent bias ( V gq ) and independent of drain quiescent bias ( V dq ). This result indicates that the current collapse of GaN HEMTs is mainly attributed to the electron injection in barrier layer under gate region. Moreover, time constants of electron emission are dependent on the V gq . At least two time constants (τ1 and τ2 ) are found to exist in the HEMTs after being switched from an off‐state ( V gq ≤ −30 V, V dq = 0 V) to an open channel condition. The τ1 and τ2 continue to increase with increasing | V gq |. It is speculated that the presence of multi‐trap energy states in barrier layer results in the quiescent bias‐dependence of time constants.